Metal Cation‐Assisted Synthesis of Amorphous B, N Co‐Doped Carbon Nanotubes for Superior Sodium Storage. Issue 20 (24th April 2020) - Fu, Ning; Liu, Ying; Liu, Rui; Wang, Xiaodong; Yang, Zhenglong
Abstract: Nearly inexhaustible sodium sources on earth make sodium ion batteries (SIBs) the best candidate for large‐scale energy storage. However, the main obstacles faced by SIBs are the low rate performance and poor cycle stability caused by the large size of Na + ions. Herein, a universal strategy for synthesizing amorphous metals encapsulated into amorphous B, N co‐doped carbon (a‐M@a‐BCN; M = Co, Ni, Mn) nanotubes by metal cation‐assisted carbonization is explored. The methodology allows tailoring the structures (e.g., length, wall thickness, and metals doping) of a‐M@a‐BCN nannotubes at the molecular level. Furthermore, the amorphous metal sulfide encapsulated into a‐BCN (a‐MS x @a‐BCN; MS x : CoS, Ni3 S2, MnS) nanotubes are obtained by one‐step sulfidation process. The a‐M@a‐BCN and a‐MS x @a‐BCN possess the larger interlayer spacing (0.40 nm) amorphous carbon nanotube rich in heteroatoms active sites, making them exhibit excellent Na + ions diffusion kinetics and capacitive storage behavior. As SIBs anodes, they show high capacity, excellent rate performance, and long cycle stability. Abstract : A facile and universal strategy to prepare the heteroatoms (N, B, M) co‐doped amorphous carbon nanotubes and their sulfurized derivatives with the short‐range large interlayer distance (0.40 nm) carbon layer and rich heteroatoms doping is explored. As sodium ion batteries anodes, the a‐M@a‐BCN and a‐MS x @a‐BCN nanotubes show superior sodium storage performance.